Sycylijski krajobraz pamięci w filmie Salvatore Giuliano (1961, reż. Francesco Rosi) - Baszak-Glebow, Ewa (Przestrzenie Teorii, 2025)
Salvatore Giuliano (dir. Francesco Rosi, 1962) tells the story of symbolic locations for the Sicilians – the Portella della Ginestra pass and the surrounding area of Montelepre in the Palermo province. These areas were the scene of conflicts between the state and the mafia, and between the peasants and the authorities. On 1st May 1947, several thousand peasants and workers gathered there during a rally organised by left-wing political parties to celebrate an electoral success and continue the campaign for agrarian reforms. The gathering was shot at by a group of armed assailants. Sicilians blame the mafia and landowners for this event. The director uses authentic landscapes of Sicily, emphasising the documentary style of the film. The landscape of Sicily in the film is also a symbol of isolation – both geographical and political. Separated from the rest of Italy, Sicily in the film appears to be a place where state law has no full power, and local conflicts unfold against the backdrop of mountainous wastelands. The article analyses the sites of memory, drawing on Pierre Nora’s theory, that make up the filmic landscape, highlighting the real issues of 1940s Sicily. The scenes shot in the mountainous regions and the Sicilian town of Montelepre evoke a sense of reportage, enhancing the credibility of the narrative and bringing the viewer closer to these historically significant events for the Sicilians.